Med Jean-Luc Nancy til Groruddalen: Et empirisk fundert bidrag til menighetsteori i lys av Nancys fellesskapskonsept - Schuerhoff, Carsten (Tidsskrift for praktisk teologi, 2025)
The paper argues for the significance of smaller groups for congregational theory through an empirical reconstruction of a charismatic group active in Oslo from the late 1970s. The group is contextualised within its local and historical environment and models of church theory are referred to. The group will also be analysed using Jean-Luc Nancy’s theory of community. In accordance with Nancy, the dissolution of the group reveals potential that is tentatively pursued in an outline of an onto-theological congregational theory.